The Relationship between Spiritual Well-Being and Social Interaction with the Resilience of Male Prisoner - Makdum Alaidin; Megah Andriany; Nur Setiawati Dewi (GLOBAL HEALTH SCIENCE GROUP, 2025)
The problem of low resilience among male correctional inmates still often occurs, such as withdrawing, tending to be offended, aggressive, easily involved in riots and attempting suicide. Male inmates are required to have good social interaction skills to be able to adapt to the prison environment and to have good spiritual well-being to prevent negative behavior from occurring. The aim of this research is to determine the relationship between spiritual well-being and social interaction with the resilience of male inmates in one of the prisons in Central Java. The research was conducted in December 2023, research design usingcross-sectional with the multiple linear regression analysis method on a population of 399 male WBP, the sampling technique used wassimple random samplingon a sample of 200 male WBPs analyzed using the testproduct moment. Data collection using questionnaires spiritual well-being scale (SWBS), social interaction, And resilience scale which first carried out validity and reliability tests on 70 WBP and was declared valid and pass the ethics test. The research show that there is a meaningful and significant relationship between spiritual well-being and social interaction on resilience, while the regression coefficient shows that spiritual well-being and social interaction have an influence on resilience of 7.6% apart from being influenced by other factors.